(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
Metadata plays a crucial role in organizing, managing, and making sense of large datasets, especially when dealing with corpora, which are extensive collections of linguistic data. Effective metadata creation ensures that a corpus is not just a collection of texts, but a well-structured resource that can be easily accessed, searched, and analyzed. This article delves into the fundamentals of metadata creation for corpora, highlighting key concepts, best practices, and the significance of metadata in linguistic research. The article examines and analyzes concepts, types of metadata. The advantages of centralizing and combining metadata are considered.